The Relationship Between the Neutrophil Percentage-to-Albumin Ratio and Rates of 28-Day Mortality in Atrial Fibrillation Patients 80 Years of Age or Older - Cai J; Li M; Wang W; Luo R; Zhang Z; Liu H (Journal of Inflammation Research, 2023)
Jiasheng Cai,1,* Mingxuan Li,2,* Wei Wang,1,* Rong Luo,1 Zheng Zhang,1 Haibo Liu1 1Department of Cardiology, QingPu Branch of Zhongshan Hospital Affiliated to Fudan University, Shanghai, 201700, People’s Republic of China; 2Department of Cardiology, Shanghai Medical College Fudan University, Huadong Hospital, Shanghai, 200040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haibo Liu; Zheng Zhang, Department of Cardiology, QingPu Branch of Zhongshan Hospital Affiliated to Fudan University, 1158 Park, Shanghai, 201700, People’s Republic of China, Email haiboliu13@fudan.edu.cn; zhangzheng@qphospital.comBackgrounds and Aims: Atrial fibrillation (AF) is the most common cardiac arrhythmia among the older patients (≥ 80 years) in clinical practice. The index of neutrophil percentage-to-albumin ratio (NPAR) is a reliable predictor of adverse outcomes in cardiovascular diseases. There is scarce evidence regarding the association between NPAR and mortality among the older patients with AF.Methods: The research was conducted among 1141 patients with AF between January 2015 and June 2020, hospitalized at Huadong Hospital affiliated with Fudan University. The primary outcome were 28-day all-cause and cardiovascular mortality. Cox regression analysis and Kaplan-Meier survival curves were used to explore the correlation between NPAR and 28-day all-cause or cardiovascular mortality. Receiver operating characteristic (ROC) curve and the area under the curve (AUC) were performed for the predictive values of NPAR on prognosis.Results: The 28-day death rate from cardiovascular disease and all-causes were 3.3% and 8.7%, respectively. Continuous NPAR levels were positively associated with all-cause (HR 1.13, 95% CI 1.09, 1.16) and cardiovascular (HR 1.16, 95% CI 1.10, 1.23) mortality after adjustment for confounding variables. Relative to patients in the T1 group, those in higher NPAR tertiles also exhibit elevated risks of all-cause (P < 0.001) and cardiovascular mortality (P < 0.001). Furthermore, both all-cause and cardiovascular mortality rates rose with increasing NPAR in all analyzed subgroups.Conclusion: NPAR values are consistently positively related to 28-day all-cause and cardiovascular mortality rates in patients ≥ 80 years of age with AF.Keywords: cardiovascular disease, neutrophil, atrial fibrillation, mortality, older